Relation between kinetic parameters for reactions of organic matter degradation in waste environmental matrix - de Almeida, Sonia [UNESP]; Bernabe, Giseli [UNESP]; Crespi, Marisa Spirandeli [UNESP]; Ribeiro, Clovis Augusto [UNESP]; Lima, Evaneide Nascimento [UNESP] (Springer, 2011)
The organic fraction of urban solid residues disposed of in sanitary landfills during the decomposition yields biogas and leachate, which are sources of pollution. Leachate is a resultant liquid from the decomposition of substances contained in solid residues and it contains in its composition organic and inorganic substances. Literature shows an increase in the use of thermoanalytical techniques to study the samples with environmental interest, this way thermogravimetry is used in this research. Thermogravimetric studies (TG curves) carried out on leachate and residues shows similarities in the thermal behavior, although presenting complex composition. Residue samples were collected from landfills, composting plants, sewage treatment stations, leachate, which after treatment, were submitted for thermal analysis. Kinetic parameters were determined using the Flynn-Wall-Ozawa method. In this case they show little divergence between the kinetic parameter that can be attributed to different decomposition reaction and presence of organic compounds in different phases of the decomposition with structures modified during degradation process and also due to experimental conditions of analysis.
Keywords: Kinetic; Landfill; Leachate; Composting; KCE